2013
DOI: 10.1007/s11147-013-9090-8
|View full text |Cite
|
Sign up to set email alerts
|

Does modeling framework matter? A comparative study of structural and reduced-form models

Abstract: This study provides a rigorous empirical comparison of structural and reduced-form credit risk frameworks. As major difference we focus on the discriminative modeling of default time. In contrast to previous literature, we calibrate both approaches to bond and equity prices. By using same input data, applying comparable estimation techniques, and assessing the out-of-sample prediction quality on same time series of CDS prices we are able to judge whether empirically the model structure itself makes an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 57 publications
3
7
0
Order By: Relevance
“…K E Y W O R D S bond spread, corporate credit risk, model combination, reduced-form model, structural model J E L C L A S S I F I C A T I O N C22, G13 J Futures Markets. Similar results for individual models are also reported by Gündüz and Homburg (2014). The formulations of the two structural models are consistent with the manager's the perspective that the firm's condition is observable and that default is an accessible stopping time.…”
supporting
confidence: 83%
See 3 more Smart Citations
“…K E Y W O R D S bond spread, corporate credit risk, model combination, reduced-form model, structural model J E L C L A S S I F I C A T I O N C22, G13 J Futures Markets. Similar results for individual models are also reported by Gündüz and Homburg (2014). The formulations of the two structural models are consistent with the manager's the perspective that the firm's condition is observable and that default is an accessible stopping time.…”
supporting
confidence: 83%
“…Similar results for individual models are also reported by Gündüz and Homburg (2014). Our data set consists of 279,826 monthly corporate bond yield spreads to the swap rate of noncallable bonds issued by industrial firms over the period 1992-2016.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Owing to its tractability, the reduced‐form approach to modeling credit risk is popular. Though there exist differences between the two approaches, Gündüz and Uhrig‐Homburg () have recently shown that their predictive powers are quite close, on average. For more details about the two approaches, please refer to Bielecki and Rutkowski (), and the references therein.…”
mentioning
confidence: 99%